16x
Both of these expressions are similar expressions, therefore you can simply add the number in front of the 'x'
6 + 10 = 16
Therefore, 6x + 10x = 16x
Answer:
Step-by-step explanation:
-13 = 5(1+4m)-2m
-13=5+20m-2m
-13=5+18m
-13-5=18m
(-13-5)/18=m
Answer:
D
Step-by-step explanation:
I'm not certain but I guess that's it
if the given point satisfies this equation then it would be its solution
(-1)=2(5)-11
-1=10-1
-1=-1
lHS=RHS
Hence (/,-1) is the solution of y=2x-11
Answer:
0.5 I think. because for every 2 on the x axis, it grows 1 on the y axis.